Legalization and Long-Term Outcomes of Immigrant Workers - Claudio Deiana; Ludovica Giua; Roberto Nisticò (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper establishes a new fact about immigration policies: legalization has long-term effects on formal employment of undocumented immigrants and their assimilation. We exploit the broad amnesty enacted in Italy in 2002 together with rich survey data collected in 2011 on a representative sample of immigrant households to estimate the effect of regularization in the long run. Immigrants who were not eligible for the amnesty have a 14% lower probability of working in the formal sector a decade later, are subject to more severe ethnic segregation on the job and display less linguistic assimilation than their regularized counterparts.
Keywords: J15; J61; K37; 330; undocumented immigrants; amnesty program; formal employment; discrimination; segregation